2019
DOI: 10.1038/s41598-019-42154-5
|View full text |Cite
|
Sign up to set email alerts
|

Lp-PLA2 activity and mass and CRP are associated with incident symptomatic peripheral arterial disease

Abstract: Long follow up is needed in prospective cohort study evaluation of plasma biomarkers for incident peripheral arterial disease (PAD) Middle-aged PAD-free individuals from the cardiovascular cohort of the Malmö Diet and Cancer study (n = 5550; 1991–94) were followed prospectively for a median time of 23.4 years. The plasma biomarkers lipoprotein-associated phospholipase A2 (Lp-PLA 2 ) activity and mass, proneurotensin, and CRP, were studied in relation to incidence of PAD until December 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The 18 articles that were not selected studied α-defensin, 21 matrix metalloproteinase 10, 59 galectin-3, 60 soluble tumor necrosis–like weak inducer of apoptosis, 61 ferritin, 62 activated protein C–protein C inhibitor complex, 63 angiopoietin-related growth factor, 64 fatty acid–binding protein 4, 65 alkyl-phosphatidylcholine and alkenylphosphatidylcholine lipids, 66 high-density lipoprotein cholesterol, 66 malondialdehyde-modified low-density lipoprotein, 67 lipoprotein-associated phospholipase A2, 68 cardiac troponin I, 69 phosphate, 70 carboxy-terminal telopeptide of type I collagen, 15 cholinesterase, 71 eicosapentaenoic acid/arachidonic acid ratio, 72 or endothelin-1. 73 …”
Section: Resultsmentioning
confidence: 99%
“…The 18 articles that were not selected studied α-defensin, 21 matrix metalloproteinase 10, 59 galectin-3, 60 soluble tumor necrosis–like weak inducer of apoptosis, 61 ferritin, 62 activated protein C–protein C inhibitor complex, 63 angiopoietin-related growth factor, 64 fatty acid–binding protein 4, 65 alkyl-phosphatidylcholine and alkenylphosphatidylcholine lipids, 66 high-density lipoprotein cholesterol, 66 malondialdehyde-modified low-density lipoprotein, 67 lipoprotein-associated phospholipase A2, 68 cardiac troponin I, 69 phosphate, 70 carboxy-terminal telopeptide of type I collagen, 15 cholinesterase, 71 eicosapentaenoic acid/arachidonic acid ratio, 72 or endothelin-1. 73 …”
Section: Resultsmentioning
confidence: 99%
“…Biomarkers analyzed in this material have previously been related to incident symptomatic arterial disease in the lower extremities. 54,55 Even though lower extremity arterial disease and carotid artery disease to some extent share similar risk factors, 56 these two arterial territories are quite different in several aspects, such as prevalence of atherosclerosis 57 and regarding hemodynamic properties. 58 In conclusion, levels of biomarkers such as NT pro-BNP and MR-proADM can be used as independent predictors for clinically detected carotid artery stenosis during longterm follow-up of subjects from the general population.…”
Section: Characteristicmentioning
confidence: 99%
“…Using patient record data, the validation showed that PAD could be confirmed in 98% of the cases, symptomatic in 97%, and only misdiagnosed in 2%. 15…”
Section: Lifestylementioning
confidence: 99%